Representation of feminine symbols in filter cigarette products - Dewi, Shinta; Al-Ghiffary, Ghalib Muhammad Syukri (Journal of Gender Equality Disability Social Inclusion and Children, 2024)
Background: Today, cigarettes are used as a consumer product by both men and women. In the past, smoking was often associated with its use by men. Over time, cigarette consumption has shifted culturally, with women becoming consumers of cigarettes with designs that emphasize elegance and a shift in consumer base. The tobacco industry adapted and began to release products aimed specifically at women, such as cigarettes with slimmer filters and more feminine packaging designs. This article discusses the changing role of filter cigarettes, which were originally associated as a symbol of femininity and are now increasingly used by men. Methods: The method used in this research is a literature study that collects, analyzes, and evaluates various relevant literature sources. Findings: This article illustrates how filter cigarettes have changed the representation of femininity and masculinity in tobacco consumption culture. Filter cigarettes were originally designed and promoted as a product that emphasized elegance, grace, and feminine imagery. However, filter cigarette consumption has shifted significantly over time, and more and more men are adopting filter cigarette products. Conclusion: Cigarette use is also influenced by the trend of e-cigarettes and the influence of social media on cigarette marketing which may lead to an increase in the number of female smokers. Novelty/Originality of this Study: This study investigates the symbolic representation of femininity in filter cigarettes, elucidating how the tobacco industry strategically employs gendered marketing to appeal to female consumers. By examining the evolution of these marketing strategies and their effects on gender norms and consumer behavior, the research offers a distinctive perspective on the intersection of gender and tobacco advertising.